The Paradox of Women's Protection: Why Women's Rights Remain Vulnerable in Cameroon Despite Legal Commitments - Nana Charles Nguindip (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Despite advancements in legal frameworks and gender equality discourse, women in Cameroon continue to face widespread rights violations, including Female Genital Mutilation, sexual abuse, child marriage, and harmful traditional practices. This persists despite Cameroon’s ratification of international instruments like CEDAW and the Maputo Protocol, raising concerns about the effectiveness of national legal and institutional responses. This study assesses the adequacy of Cameroon’s legal framework—specifically the Constitution, Penal Code, and Civil Code in addressing violence against women. Using a qualitative-descriptive approach with document and normative legal analysis, the research draws on primary legal texts and secondary sources such as institutional reports and academic literature. The findings reveal a significant gap between legal commitments and enforcement, highlighting the absence of a comprehensive law on violence against women and persistent societal and institutional barriers. The study calls for stronger legal reforms, improved implementation, and greater public awareness to ensure effective protection of women’s rights.